Business Sustainability – A Marketing Perspective - Narayan, G.V. (International Journal of Advanced Science and Technology, 2019)
Background Today all businesses are evolving fromthe single bottom line goal of profit maximization to an inclusive, more responsible triple bottom-line objectives of Economic, Social and Ecological Sustainability.But the relationship between the traditionalconcept of marketing function with a focus on profit maximization has a distraught relationship with the concept of Sustainability. Purpose This conceptual paper is an effort to throw light on the importance of Sustainability in Business as a long time strategy. This study is to recognize the importance of Long time perspective considering the Social & Environmental dimensions in addition to the Economic Goals as well as Accountability of Business to future generations in addition to present stakeholders. Design / Methodology /Approach This conceptual paper provides a literature review of a study about Business Sustainability from the perspective of Marketing.The study is based on secondary datacollected from previous researches and studies. This study covers the major aspects of Business Sustainability marketing such as, Sustainable Marketing ,How sustainability affects marketing practices, Need for a Change in Thinking, Meaning of Marketing Sustainability – A practical look, Sustainability Strategy, Barriers to successful implementation of sustainability initiatives, Organisations that have successfully implemented Sustainability Strategies, and finally Sustainability & Market Logic. Findings Findingsreflect the Priorities of Traditional Marketing Concepts, Priorities of Sustainable Business Concepts, Sustainable Marketing Strategies, Changes needed for evolving into a Sustainable Marketing entity. Practical Implications / Value Effort is made to compare evolution of Traditional Marketing into Sustainable Marketing with some Best Practices & strategies adopted by companies.Some of the strategies and practices followed by Global Business.Reflections on the general directions of change in Business Environment focus from Short term to Long Term priorities. Keyword:. Business Sustainability,Sustainability Marketing,Sustainability Strategy, Sustainability Barriers,Sustainability & Market Logic, Traditional & Sustainable Marketing. Paper Type: ConceptualPaper